Moringa Leaf Extract Capsules Enriched with Royal Jelly on Cortisol and Stress - Dwi Kartika Sari; Veni Hadju; Werna Nontji; Mardiana Ahmad; Aryadi Arsyad; Andi Nilawati Usman; Yudi Yanto; Taqwin Taqwin (Jurnal Kesehatan Masyarakat, 2025)
During pregnancy, physiological and psychological changes often increase stress and cortisol levels. Administering moringa leaf extract capsules fortified with royal jelly presents a viable intervention to alleviate this stress. This study investigates the specific effects of these capsules on cortisol and stress levels in pregnant women. The study was conducted as a true experimental, single-blind, randomized controlled trial involving 61 pregnant women. The intervention group (n = 31) received moringa leaf extract capsules enriched with royal jelly, while the control group (n = 30) received multi-micronutrient supplements. The findings revealed a noteworthy reduction in cortisol levels within the intervention group (p = 0.030), from 26.61 ± 8.15 to 19.98 ± 14.00, as well as in the control group (p = 0.003), from 21.13 ± 7.76 to 13.26 ± 16.09. Likewise, stress levels exhibited a significant decrease within the intervention group (p = 0.016), decreasing from 18.68 ± 3.74 to 28.75 ± 15.02, and the control group (p = 0.000), declining from 19.17 ± 3.64 to 16.20 ± 3.38. Moringa leaf extract capsules enriched with royal jelly, as a natural remedy, merit the recommendation for inclusion in initiatives to enhance maternal and infant health.